Pengaruh manajemen konflik dan efikasi diri terhadap kinerja karyawan pada PT Meerkats Flexipack Indonesia - Semuel, Semuel (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2024)
This study aims to determine whether there is an influence of Conflict Management, Self Efficacy on employee performance at PT Meerkats Flexipack Indonesia. Employee performance is the overall output produced by employees where in the process of work there is punctuality, maximum quality, sufficient skills where all of them can help the company to achieve a goal. The population in this study is PT Meerkats Flexipack Indonesia, this study uses saturated samples, saturated samples are samples that represent the total population. Or in other words, all members of the population are sampled. The method in this study is Quantitative, the data analysis used in this study is multiple linear regression analysis. The data collection technique used is by distributing questionnaires. Multiple linear regression analysis techniques were performed using SPSS software version 27 for windows. The result of this study is that independent and dependent variables have a partial and simultaneous effect. The result of the coefficient of determination (R2) of the R Square value is 0.534 which means that the independent variable affects the dependent variable by 0.534 or presented to 53.4%, while the remaining 46.6% is explained by other variables that are not included in this study.